The Electrochemical Oxidation and Mass Transfer Mechanism of Formic Acid on the Catalyst Electrode Surface - Hu, Jie; Wang, Panpan; Chen, Changguo (Frontiers in Chemistry, 2022)
The organic small molecule fuel battery has attracted wild attention in recent years. Unfortunately, the inherent catalyst poisoning phenomenon hinder its commercialization. Exploring the anodic catalytic reaction mechanism is urgent. In this paper, the nucleation mechanism of HCOOH on catalyst electrode surface is investigated. The electrochemical results indicate that the HCOOH oxidation conform to two-dimensional instantaneous nucleation process. The corresponding adsorption model of CO on catalyst surface was established finally.